Perancangan Tempat Sampah Pintar Berbasis IoT Pada Rumah Sakit Umum Sungailiat - Muhammad Faqih Taqiyuddin Haqani; Muhammad Ega Rivanda; Yudhi Yudhi; Parulian Silalahi (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
This study presents the implementation of an IoT-based smart waste bin designed for hospital environments to monitor waste capacity and detect hazardous medical waste (B3). Effective waste management in hospitals is critical to prevent contamination and ensure environmental safety. The proposed system integrates ultrasonic sensors to measure waste capacity and an MQ-135 gas sensor to detect hazardous gases, controlled by an ESP32 microcontroller. Waste status data are transmitted in real time to a mobile monitoring application via an IoT platform, enabling automatic notifications when waste reaches critical capacity levels. Experimental results show that the system can measure waste levels with an accuracy of ±2 cm and deliver notifications with an average latency below 2 seconds. The proposed system demonstrates potential to improve efficiency, safety, and responsiveness in hospital waste management.